Tourism Destination Development in Semarang City - Qristin Violinda; Efriyani Sumastuti (International Journal of Halal System and Sustainability, 2022)
Tourism is a strategic sector that has a high multiplier effect on other sectors. The development of the tourism sector will have a positive impact on improving other sectors such as the trade, hotel and restaurant, transportation, and other sectors. This has caused many regions to do their utmost to develop this sector. Empowerment of natural, cultural and culinary potentials as an attraction of tourism is still not optimal. Management of tourist attractions that exist today is also not optimal. Even the involvement of related parties in this matter can be said to have not been maximized. Ideally, the development of tourist destinations should have the involvement of tourism operators, namely the government, the private sector and the community. Seeing this phenomenon with its various problems, it is very interesting to conduct research. This research used quantitative research method with five destination. The results of the N.Vivo analysis show that of the twenty factors analyzed there are three factors that most influence on tourism excellence in the city of Semarang. These three factors include: Government and private assistance, tourism promotion, community involvement.